Aphthous Esophagael Ulceration: A Novel Presentation of Crohn’s Disease? - Paul L Beck; Philip K Blustein; Melvin A Andersen (Canadian Journal of Gastroenterology)
Crohn’s disease (CD) commonly presents as involvement of the small bowel or colon - the esophagus is rarely involved. The authors describe the case of a 45-year-old woman who presented with odynophagia and was found to have aphthous ulcers of the esophagus. On questioning, she admitted to three to four episodes of nonbloody diarrhea, each lasting less than one week, over the past two years. The patient denied other symptoms of gastrointestinal, collagen-vascular, respiratory or cardiovascular disease. Viral, fungal and bacterial cultures of blood, stool and tissue biopsies were all negative. A small bowel enema showed inflammation of the distal ileum. Colonoscopy revealed patchy areas of inflammation of the colon and distal ileum. Biopsies from the esophagus, duodenum, terminal ileum and colon showed chronic inflammation, lymphoid aggregates, goblet cell hyperplasia (in the colon) and crypt abscesses. Giant cells, granulomas and fissures were not evident in any of the biopsies. The patient failed to respond to a three-week course of omeprazole, but her symptoms resolved within three days of starting prednisone. The exact cause of the esophageal ulcerations is unknown but most likely is CD of the esophagus.